2001
DOI: 10.2174/1381612013398103
|View full text |Cite
|
Sign up to set email alerts
|

Endurance Exercise Training and Reproductive Endocrine Dysfunction in Men Alterations in the Hypothalamic-Pituitary-Testicular Axis

Abstract: Research indicates that endurance exercise training has significant effects upon the reproductive endocrine system of humans. Until recently, this effect was thought to be limited primarily to women. However, a growing body of evidence demonstrates that the male reproductive endocrine system is also effected. Specifically, the circulating hormonal levels of testosterone are found to be at low concentrations; and, the hypothalamic-pituitary-testicular axis that regulates testosterone production is altered in en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
60
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 51 publications
10
60
0
Order By: Relevance
“…When testosterone levels are compared cross-sectionally between middle-aged and older men who have engaged in longterm exercise versus those who have not, testosterone levels are higher among regular exercisers (3,40), with similar findings for SHBG (10). However, among highly trained endurance athletes, testosterone levels have also been found to be lower than among either resistance-trained or control subjects, introducing the possibility of exercise-related sex hormone dysfunction (17). We found no effect of our 12-month moderate-to-vigorous aerobic training program on circulating testosterone levels, suggesting that it is unlikely testosterone would mediate the beneficial effects of this type of exercise such as altered body composition or improved bone health.…”
Section: Discussionmentioning
confidence: 73%
“…When testosterone levels are compared cross-sectionally between middle-aged and older men who have engaged in longterm exercise versus those who have not, testosterone levels are higher among regular exercisers (3,40), with similar findings for SHBG (10). However, among highly trained endurance athletes, testosterone levels have also been found to be lower than among either resistance-trained or control subjects, introducing the possibility of exercise-related sex hormone dysfunction (17). We found no effect of our 12-month moderate-to-vigorous aerobic training program on circulating testosterone levels, suggesting that it is unlikely testosterone would mediate the beneficial effects of this type of exercise such as altered body composition or improved bone health.…”
Section: Discussionmentioning
confidence: 73%
“…10,57,70 The continued elevation of AST suggests muscle permeability remains increased, allowing enzymes to leak into circulation. 41 Parallel to AST, ALT concentrations increased immediately postrace and remained elevated at D1 and D2. Our findings are consistent in magnitude and duration with previous results from a 24-hour ultramarathon held in Soo-Chow, China.…”
Section: Discussionmentioning
confidence: 90%
“…Some researchers have also suggested that a low testosterone level may provide a favorable environment to mobilize amino acids away from protein synthesis and redirect them to gluconeogenesis. 39,40 In addition, some studies have found a low testosterone concentration may have cardiovascular benefits, 41 as well as increase high-density lipoprotein in men. 42 Again, such benefits remain highly speculative because of the importance of normal homeostatic concentrations of testosterone in mediating a host of metabolic and cellular signaling systems for normal health and development.…”
Section: Discussionmentioning
confidence: 99%
“…As previously discussed it may permit the mobilization of fuels for recovery and restoration of glycogen stores. Others have suggested that lower testosterone levels could have a cardioprotective effect (Hackney 2001). Lower testosterone levels and reduced protein synthesis could also be a selective adaptation that is beneficial to endurance athletes by limiting the development of muscle mass (Hackney et al 2003).…”
Section: Sessionmentioning
confidence: 99%